Latino College Students: Cultural Socialization and Mental Health Benefits from Seeking Food at the Campus Food Pantry - David Magallanes Cortes:::::: (2023)
As I wanted to pursue graduate school and due to the of lack of research experience, I decided to do an independent study with one of my professors and I knew that I wanted to research something around the Latino community as I identify as Latino. My professor shared with me a finding from the Cougar Pantry report, Latinos reported mental health benefits from using the pantry, and that no other ethnic or racial group reported mental health benefits from using the pantry. The CSUSM Library Award for Undergraduate Research, Scholarship and Creative Activity recognizes undergraduate students who demonstrate sophistication and originality in research projects and creative works, and reflection upon the research/creation process. Up to six prizes will be awarded in three categories: Creative Works, Empirical Research and Interpretive Analysis. Winners receive a cash prize and public recognition of their excellent work. Submissions by individuals or groups will be considered in the following three categories: Creative Works, including, but not limited to, an art installation, software program, musical composition, film or video, special project, etc. Empirical Research, including, but not limited to, research conducted with qualitative or quantitative methodologies using the (social-) scientific method. Interpretive Analysis, including, but not limited to, analysis which aims to capture hidden meaning and ambiguity of a cultural artifact.